Streptozotocin-induced leukocyte DNA damage in rats - Sinzato, Yuri Karen [UNESP]; Gelaleti, Rafael Bottaro [UNESP]; Volpato, Gustavo Tadeu; Rudge, Marilza Vieira Cunha [UNESP]; Herrera, Emilio; Damasceno, Débora Cristina [UNESP] (Taylor & Francis, 2018)
Although several studies using peripheral blood samples suggest that DNA damage is caused by streptozotocin (STZ) per se, our hypothesis is that DNA damage is caused by STZ-induced glycemic changes. Thus, we aimed at evaluating DNA damage levels in peripheral blood samples from rats at different time points within the first 24 h after a single intravenous dose of STZ. Female Wistar rats (control, n = 8; STZ, n = 7) were administered a single STZ intravenous injection (40 mg/kg body weight). Blood samples were collected from the tail vein for genotoxicity analysis by comet assay and glycemia assessment before STZ administration (time point zero) and at 2, 4, 6, 8, 12, and 24 h afterward. At 2 h, there was initial hyperglycemia associated with STZ-induced glycogenolysis that caused an increase in leukocyte DNA damage levels. At 4 h, glycemic and DNA damage levels were normalized. However, at 6 and 8 h, we observed hypoglycemia concomitant with increased DNA damage levels. From 10 h onward up to 24 h, DNA damage persisted and hyperglycemia appeared. Thus, DNA damage increased soon after both hypoglycemia and hyperglycemia, which were not directly induced by STZ owing to its known short life. In conclusion, increased peripheral blood DNA damage levels within 24 h after STZ administration in rats are associated with abnormal glycemic levels and their complications rather than with STZ per se.
Keywords: comet assay; Genotoxicity; hyperglycemia; rats; streptozotocin